Rootstock effect on horticultural performance and fruit quality is not uniform across five commercial apple cultivars in western New York - Lawrence, Brian T.; Fazio, Gennaro; Nieto, Luis Gonzalez; Robinson, Terence L. (Frontiers in Plant Science, 2025)
IntroductionThe interactive effect of different apple scions with commonly used rootstocks could result in growers selecting an inferior option for tree survival, yield, and fruit quality.MethodsThe long-term tree performance and fruit quality interactions of 19 rootstocks (including Budagovsky, Geneva, and Malling series) and 5 apple cultivars (‘Empire’, ‘Gala’, ‘Honeycrisp’, ‘Mustu’, and ‘Delicious’) were explored in two orchards in Western New York. The first orchard examined the five cultivars on dwarfing rootstocks (B.9, CG.4210, G.11, G.16, G.202, G.41, G.65, G.814, M.26, M.9Pajam2, and M.9T337) and was planted at a spacing of 1.22 m x 3.66 m (2,243 trees ha-1). The second orchard examined the same cultivars on semi-dwarfing rootstocks (B.118, G.214, G.30, G.210, G.935, G.222, M.26, and M.7) and was planted at a spacing of 1.83 m x 4.27 m (1,282 trees ha-1). ResultsFollowing 17 years, the variables of tree mortality, growth, cumulative yield, and cumulative yield efficiency each resulted in a significant interaction between cultivar and rootstock in both orchards. There were no significant interactions on quality variables measured except fruit color of the 3 bi-colored ‘Gala’, ‘Honeycrisp’ and ‘Delicious’ for both the dwarfing and semi-dwarfing rootstocks. Discussion/ConclusionsThe implications of the interactions observed are that apple producers should pair specific rootstocks with specific cultivars to optimize orchard performance.